2014
DOI: 10.1016/j.recli.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Violence against women during pregnancy: sistematized revision

Abstract: r e p r o d c l i m . 2 0 1 4;2 9(2):71-79 Reprodução & Climatério h t t p : / / w w w . s b r h . o r g . b r / r e v i s t a Violence against women Domestic violence Pregnancy a b s t r a c tViolence against women is widely recognized as a serious public health problem. The pregnancy is a risk factor for increasing the violence, especially when it is related to socioeconomic conditions. The objective of this work is to ascertain the relation between violence against women during pregnancy in developed countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 28 publications
2
21
0
10
Order By: Relevance
“…A review of the literature did not identify studies using socioeconomic status, social support and violence as constructs or using structural equation modeling in their analyses [15,8]. A limitation of the present study was the fact that the subjects from both samples were part of a convenience sample that was not representative of the entire population of pregnant women in the municipalities.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A review of the literature did not identify studies using socioeconomic status, social support and violence as constructs or using structural equation modeling in their analyses [15,8]. A limitation of the present study was the fact that the subjects from both samples were part of a convenience sample that was not representative of the entire population of pregnant women in the municipalities.…”
Section: Discussionmentioning
confidence: 96%
“…Because of these high rates and negative repercussions on the health and life of women and their children, several studies have sought to identify factors associated with violence during pregnancy, among them, socioeconomic status (SES) and social support [1,2,4,8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence abounds that spousal violence is prevalent with deleterious effects on women’s health across the world [ 27 29 ]. It is more worrisome that spousal violence is also widely reported against pregnant women [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance a multicentre study coordinated by the WHO found out that the prevalence of partner violence against women generally varies between 15% in Japan and 71% in Ethiopia. 1,12 Substituting the values in the above formula gives 200% (to the nearest ten). A convenient sampling method was used and pregnant women were recruited conveniently as they came into the clinic.…”
Section: Introductionmentioning
confidence: 99%